Positive electrode and non-aqueous electrolyte secondary battery having the same
By using high nickel content lithium composite oxide and multi-layer structural surfactant in the positive electrode active material layer of the lithium ion secondary battery, the problem of gas generation at high voltage is solved, and high impregnability and stability are achieved.
Patent Information
- Application Number
- CN202210327007.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-03-30
AI Technical Summary
When using lithium composite oxide with high nickel content as the positive electrode active substance, the problem of decomposing the surfactant at a high voltage causes gas to occur.
A multilayer structure of a positive electrode is designed, in which the positive electrode active material layer contains 70 mol% or more of nickel with respect to lithium composite oxides of metal atoms other than lithium, and two or more layers of surfactant are used in this layer, and the mass ratio of the surfactant is 1.0 mass% or more and 10 mass% or less to form excellent non-aqueous electrolyte impregnability and suppress gas generation.
It is achieved to suppress gas generation under high voltage, and at the same time improve the impregnation of the nonaqueous electrolyte to the positive electrode active material layer, and improve the performance and stability of the battery.
Smart Images

Figure CN115148993B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode and a non-aqueous electrolyte secondary battery having the positive electrode. Background Art
[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries have been suitably used in portable power sources for personal computers and portable terminals, and vehicle driving power sources for electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs).
[0003] The positive electrode of a non-aqueous electrolyte secondary battery generally has a structure in which a positive electrode active material layer containing a positive electrode active material is supported on a positive electrode current collector. In the past, the following technology is known: by making the positive electrode active material layer contain a surfactant, the wettability of the positive electrode active material layer to the non-aqueous electrolyte is improved, and the impregnation of the non-aqueous electrolyte into the positive electrode active material layer is improved (for example, refer to patent documents 1 to 3).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-526349
[0007] Patent Document 2: Japanese Patent Application Publication No. 2008-21415
[0008] Patent Document 3: Japanese Patent Application Publication No. 2015-201309 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, as a result of intensive research conducted by the present inventors, it has been newly discovered that in the technology of making the positive electrode active material layer contain a surfactant, when a lithium composite oxide with a high nickel (Ni) content is used as the positive electrode active material, there is a problem of the surfactant decomposing at a high voltage to generate gas.
[0011] Therefore, an object of the present invention is to provide a positive electrode comprising a positive electrode active material layer containing a lithium composite oxide with a high Ni content and a surfactant, wherein the positive electrode active material layer has excellent impregnation properties with a nonaqueous electrolyte and gas generation at a high voltage is suppressed.
[0012] Means for solving problems
[0013] The positive electrode disclosed herein comprises a positive electrode collector and a positive electrode active material layer supported on the positive electrode collector. The positive electrode active material layer contains a positive electrode active material and a surfactant. The positive electrode active material comprises a lithium composite oxide in which the content of nickel relative to metal atoms other than lithium is 70 mol% or more. The positive electrode active material layer has a multilayer structure comprising two or more layers in which the mass ratio of the surfactant relative to the total of the positive electrode active material and the surfactant is different. In the layer in which the mass ratio of the surfactant in the layer included in the multilayer structure is large, the mass ratio of the surfactant is greater than 1.0 mass % and less than 10 mass %. According to such a structure, a positive electrode can be provided, which is a positive electrode having a positive electrode active material layer containing a lithium composite oxide with a high Ni content and a surfactant, wherein the impregnation of the non-aqueous electrolyte into the positive electrode active material layer is excellent and gas generation under high voltage is suppressed.
[0014] In a preferred embodiment of the positive electrode disclosed herein, in the layer having a small mass ratio of the surfactant among the layers included in the multilayer structure, the mass ratio of the surfactant is 0.5 mass % or less. According to such a configuration, gas generation can be further suppressed.
[0015] In a preferred embodiment of the positive electrode disclosed herein, the ratio of the thickness of the layer containing a large mass ratio of the surfactant to the thickness of the layer containing a small mass ratio of the surfactant is 0.1 to 0.5. With such a configuration, gas generation can be further suppressed.
[0016] In a preferred embodiment of the positive electrode disclosed herein, in the layer having a large mass ratio of the surfactant, the mass ratio of the surfactant is 1.0 mass % or more and 5.0 mass % or less. According to such a configuration, gas generation can be further suppressed.
[0017] In a preferred embodiment of the positive electrode disclosed herein, the surfactant is a nonionic surfactant. According to such a configuration, gas generation can be further suppressed.
[0018] In a preferred embodiment of the positive electrode disclosed herein, in the layer having a large mass ratio of the surfactant, the coverage of the positive electrode active material with the surfactant is 5% to 50%. With such a configuration, gas generation can be further suppressed.
[0019] In a preferred embodiment of the positive electrode disclosed herein, the layer having a large mass ratio of the surfactant contains a single particle of positive electrode active material. According to such a configuration, the impregnation of the positive electrode active material layer with the nonaqueous electrolyte solution is further enhanced.
[0020] From another perspective, the nonaqueous electrolyte secondary battery disclosed herein comprises the positive electrode, the negative electrode and the nonaqueous electrolyte. According to such a configuration, a nonaqueous electrolyte secondary battery having excellent impregnation of the nonaqueous electrolyte into the positive electrode active material layer and suppressing gas generation at high voltage can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 2 is a cross-sectional view schematically showing the structure of a positive electrode according to a first embodiment of the present invention.
[0022] Figure 2 2 is a cross-sectional view schematically showing the structure of a positive electrode according to a second embodiment of the present invention.
[0023] Figure 3 2 is a cross-sectional view schematically showing the structure of a positive electrode according to a third embodiment of the present invention.
[0024] Figure 4 is a cross-sectional view schematically showing the internal structure of a lithium ion secondary battery according to one embodiment of the present invention.
[0025] Figure 5 This is a schematic exploded view showing the structure of a wound electrode body of a lithium ion secondary battery according to one embodiment of the present invention.
[0026] Description of Reference Numerals
[0027] 20 Wound electrode body
[0028] 30 Battery housing
[0029] 36 Safety valve
[0030] 42 Positive terminal
[0031] 42a Positive electrode collector plate
[0032] 44 Negative terminal
[0033] 44a Negative electrode collector plate
[0034] 50 positive electrode sheet (positive electrode)
[0035] 52 positive electrode collector
[0036] 52a Positive electrode active material layer non-formed portion
[0037] 54 Positive electrode active material layer
[0038] 60 Negative electrode sheet (negative electrode)
[0039] 62 negative electrode collector
[0040] 62a Negative electrode active material layer non-formed portion
[0041] 64 Negative electrode active material layer
[0042] 70 separator sheet (separator)
[0043] 80 Non-aqueous electrolyte
[0044] 100 Lithium-ion secondary battery DETAILED DESCRIPTION
[0045] Below, while referring to the attached Figure 1 The embodiments of the present invention are described. It should be noted that matters required for the implementation of the present invention that are not mentioned in this specification can be understood as design matters for those skilled in the art based on the prior art in this field. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, the same figure numbers are marked for components and parts that play the same role for description. In addition, the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships.
[0046] It should be noted that in this specification, "secondary battery" refers to a storage device that can be repeatedly charged and discharged, and is a term that includes storage elements such as so-called storage batteries and double-layer capacitors. In addition, in this specification, "lithium-ion secondary battery" refers to a secondary battery that uses lithium ions as charge carriers and realizes charging and discharging by the movement of charges accompanied by lithium ions between positive and negative electrodes.
[0047] [First embodiment]
[0048] exist Figure 1 The first embodiment is shown as an example of the positive electrode disclosed herein. As shown in the figure, the positive electrode 50 of the first embodiment includes a positive electrode collector 52 and a positive electrode active material layer 54 supported on the positive electrode collector 52. In the example shown in the figure, the positive electrode active material layer 54 is provided on both sides of the positive electrode collector 52, but it can also be provided on a single side. The positive electrode active material layer 54 is preferably provided on both sides of the positive electrode collector 52.
[0049] As shown in the figure, the positive electrode 50 may have a positive active material layer non-formed portion 52a at at least one end where the positive active material layer 54 is not formed and the positive current collector 52 is exposed. The positive active material layer non-formed portion 52a functions as a current collecting portion (particularly a collector tab).
[0050] As the positive electrode current collector 52, a sheet or foil of a metal such as aluminum, nickel, titanium, stainless steel, etc. can be used, and aluminum foil is preferably used. When aluminum foil is used as the positive electrode current collector 52, there is no particular limitation on its thickness, and it is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.
[0051] As shown in the figure, the positive electrode active material layer 54 has a multilayer structure including a layer 54A located on the positive electrode collector 52 side and a layer 54B located on the surface layer side. It should be noted that the layer 54A and the layer 54B are only shown on one side of the positive electrode active material layer 54, but in the first embodiment, the positive electrode active material layer 54 on both sides has the layer 54A and the layer 54B. However, the positive electrode active material layer 54 on only one side may have a multilayer structure including the layer 54A and the layer 54B.
[0052] The positive electrode active material layer 54 (ie, each of the layer 54A and the layer 54B) contains a lithium composite oxide containing 70 mol % or more of nickel relative to metal atoms other than lithium (hereinafter also referred to as “lithium composite oxide having a high Ni content”) as a positive electrode active material.
[0053] The type of lithium composite oxide containing high Ni is not particularly limited as long as the Ni content relative to the metal atoms other than lithium is 70 mol% or more. The lithium composite oxide containing high Ni preferably has a layered rock salt type crystal structure. Examples of such lithium composite oxides include lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and the like.
[0054] It should be noted that in this specification, "lithium nickel cobalt manganese composite oxide" refers to a term that includes oxides containing one or more additional elements other than these elements, in addition to oxides containing Li, Ni, Co, Mn, and O as constituent elements. Examples of the additional elements include transition metal elements such as Mg, Ba, Sr, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, K, Fe, Cu, Zn, and Sn, and typical metal elements. In addition, the additional elements may also be semi-metallic elements such as B, C, Si, and P, and non-metallic elements such as S, F, Cl, Br, and I. This is also the same for the above-mentioned lithium nickel cobalt aluminum composite oxides.
[0055] As a lithium composite oxide containing a high amount of Ni, a lithium nickel cobalt manganese composite oxide is preferred because it can impart various advantageous properties to the lithium ion secondary battery 100. As a lithium nickel cobalt manganese composite oxide, a lithium nickel cobalt manganese composite oxide having a composition represented by the following formula (I) is preferred.
[0056] Li 1+x Ni y Co z Mn (1-y-z) M α O 2-β Q β (I)
[0057] In formula (I), x, y, z, α and β respectively satisfy -0.3≦x≦0.3, 0.7≦y≦0.95, 0.02≦z≦0.28, 0≦α≦0.1, and 0≦β≦0.5. M is at least one element selected from Al, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, Ti and Si. Q is at least one element selected from F, Cl and Br. x preferably satisfies 0≦x≦0.3, more preferably satisfies 0≦x≦0.15, and further preferably is 0. From the viewpoint of energy density, y preferably satisfies 0.75≦y≦0.95. z preferably satisfies 0.03≦z≦0.22. α preferably satisfies 0≦α≦0.05, and is more preferably 0. β preferably satisfies 0≦β≦0.1, and is more preferably 0.
[0058] The positive electrode active material layer 54 may contain positive electrode active materials other than the lithium composite oxide containing high Ni content within a range that does not hinder the effect of the present invention. The positive electrode active material may be used alone or in combination of two or more. The layer 54A and the layer 54B may contain the same positive electrode active material or different positive electrode active materials.
[0059] The content of the positive electrode active material is not particularly limited, but is preferably 70 mass % or more, more preferably 80 mass % or more, and further preferably 85 mass % or more in the positive electrode active material layer 54 (ie, relative to the total mass of the positive electrode active material).
[0060] There is no particular restriction on the average particle size (median particle size D50) of the positive electrode active material, for example, 0.05 μm or more and 25 μm or less, preferably 0.5 μm or more and 23 μm or less, more preferably 3 μm or more and 22 μm or less. It should be noted that the average particle size (median particle size D50) of the positive electrode active material can be obtained, for example, by laser diffraction scattering method.
[0061] In addition, the positive electrode active material layer 54 contains a surfactant. The surfactant can use a known surfactant used in the positive electrode active material layer in the past and a surfactant having the same or more characteristics as the surfactant. Specifically, as the surfactant, a cationic surfactant, an anionic surfactant, an amphoteric surfactant, a nonionic surfactant, etc. can be used. They can be used alone or in combination of two or more.
[0062] Examples of the cationic surfactant include mono- and di-long-chain alkyl quaternary ammonium salts such as alkyltrimethylammonium chloride and dialkyldimethylammonium chloride; and alkylamine salts.
[0063] Examples of anionic surfactants include alkylbenzene sulfonates, alkyl sulfates, alkyl ether sulfates, alkenyl ether sulfates, alkenyl sulfates, α-olefin sulfonates, α-sulfofatty acids or their ester salts, alkyl sulfonates, saturated fatty acid salts, unsaturated fatty acid salts, alkyl ether carboxylates, alkenyl ether carboxylates, amino acid-type surfactants, N-acylamino acid-type surfactants, alkyl phosphates or their salts, alkenyl phosphates or their salts, and alkyl sulfosuccinates.
[0064] Examples of the amphoteric surfactant include a carboxyl-type amphoteric surfactant and a sulfobetaine-type amphoteric surfactant.
[0065] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyethylene glycol dimethyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, and polyoxyethylene higher alkyl ethers; polyoxyethylene alkylaryl ethers such as polyoxyethylene nonylphenyl ether; polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, and polyoxyethylene sorbitan trioleate; sucrose fatty acid esters; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan tetraoleate; polyethylene glycol; Polyoxyethylene fatty acid esters such as polyethylene glycol monolaurate, polyethylene glycol monostearate, polyethylene glycol distearate, and polyethylene glycol monooleate; polyoxyethylene alkylamines; polyoxyethylene hydrogenated castor oil; block copolymers of ethylene oxide and propylene oxide; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan sesquioleate, and sorbitan distearate; glycerol fatty acid esters such as glycerol monostearate, glycerol monooleate, diglycerol monooleate, and self-emulsifying glycerol monostearate; alkyl alkanolamides, etc.
[0066] As the surfactant, a nonionic surfactant is preferred from the viewpoint that the impregnation of the nonaqueous electrolyte into the positive electrode active material layer 54 becomes particularly high and the amount of gas generated becomes particularly small. As the nonionic surfactant, a polyoxyethylene surfactant (i.e., a surfactant containing a polyoxyethylene unit) is preferred, and a polyoxyethylene alkyl ether is more preferred.
[0067] There is no particular restriction on the existence form of the surfactant in the positive electrode active material layer 54, and the surfactant preferably exists by coating the positive electrode active material. At this time, the coverage of the positive electrode active material using the surfactant is preferably greater than 5% and less than 50%, and more preferably greater than 10% and less than 30%. As for the coverage, for example, the positive electrode active material coated with the surfactant is measured by X-ray photoelectron spectroscopy (XPS), and the coverage can be calculated using its spectral intensity. Alternatively, the element distribution of the positive electrode active material coated with the surfactant is observed using an electron microscope, and the coverage can be calculated based on the proportion of the exposed surface of the positive electrode active material.
[0068] The coating of the positive electrode active material using a surfactant can be performed by a known method (dry method, wet method). In the dry method, for example, by mixing the surfactant and the positive electrode active material using a high-speed stirrer, the coating of the positive electrode active material using a surfactant can be performed. In the wet method, for example, after adding a surfactant to the positive electrode composite slurry used to form the positive electrode active material layer 54 and mixing, the positive electrode composite slurry is applied to the positive electrode collector 52 and dried, thereby enabling the coating of the positive electrode active material using a surfactant.
[0069] The positive electrode active material layer 54 may contain components other than the positive electrode active material and the surfactant. Examples thereof include lithium phosphate (Li 3 PO 4 ), conductive materials, adhesives, etc.
[0070] The content of lithium phosphate in the positive electrode active material layer 54 is not particularly limited, but is preferably 1 mass % to 15 mass %, and more preferably 2 mass % to 12 mass %.
[0071] As the conductive material, carbon black such as acetylene black (AB) or other carbon materials such as graphite can be preferably used. There is no particular limitation on the content of the conductive material in the positive electrode active material layer 54, and for example, it is 0.1 mass % or more and 20 mass % or less, preferably 1 mass % or more and 15 mass % or less, and more preferably 2 mass % or more and 10 mass % or less.
[0072] As a binder, for example, polyvinylidene fluoride (PVdF) etc. can be used. There is no particular limitation on the content of the binder in the positive electrode active material layer 54, and for example, it is 0.5 mass % or more and 15 mass % or less, preferably 1 mass % or more and 10 mass % or less, and more preferably 1.5 mass % or more and 8 mass % or less.
[0073] In the positive electrode active material layer 54, the mass ratio of the surfactant to the total of the positive electrode active material and the surfactant is different in layer 54A and layer 54B (hereinafter, the mass ratio of the surfactant to the total of the positive electrode active material and the surfactant is also referred to as "mass ratio (S) of the surfactant" or simply "mass ratio (S)"). Therefore, the mass ratio (S) of the surfactant is large in one layer. In the present embodiment, the mass ratio (S) of the surfactant in layer 54B is larger than that in layer 54A. In layer 54B where the mass ratio (S) of the surfactant is large, the mass ratio (S) of the surfactant is greater than 1.0 mass% and less than 10 mass%.
[0074] Thus, in this embodiment, the positive electrode active material layer 54 is set to a multilayer structure, so that the surfactant is more biased in one layer (non-uniformly distributed). In addition, the amount of the surfactant in the layer where the surfactant is biased is specified. Thus, the layer is set as a flow path for the non-aqueous electrolyte to penetrate in the positive electrode active material layer 54, thereby improving the electrolyte impregnation, and the amount of the surfactant as the whole of the positive electrode active material layer 54 is reduced, which can suppress the generation of gas under high voltage.
[0075] From the viewpoint of further reducing gas generation, in the layer 54B having a large mass ratio (S) of the surfactant, the mass ratio (S) of the surfactant is preferably 1.0 mass % or more and 5.0 mass % or less.
[0076] The mass ratio (S) in layer 54A is not particularly limited as long as it is smaller than the mass ratio (S) in layer 54B. The mass ratio (S) in layer 54A is preferably less than half of the mass ratio (S) in layer 54B (i.e., less than 50%), and more preferably less than 20%. The mass ratio (S) in layer 54A may be 0 mass%. The mass ratio (S) in layer 54A is preferably less than 1.0 mass%, more preferably less than 0.5 mass%, and further preferably less than 0.2 mass%.
[0077] The mass ratio (S) of the surfactant can be determined, for example, by simultaneous thermogravimetric and differential thermal analysis (TG-DTA measurement) under a nitrogen atmosphere.
[0078] There is no particular restriction on the ratio of the thickness of layer 54B having a larger mass proportion (S) of the surfactant to the thickness of layer 54A having a smaller mass proportion (S) of the surfactant (layer 54B / layer 54A). From the viewpoint of further reducing gas generation, the ratio is preferably greater than 0.1 and less than 1.0, and more preferably greater than 0.1 and less than 0.5.
[0079] The total thickness of the positive electrode active material layer 54 (ie, the total thickness of the multilayer structure layer 54A and layer 54B) is not particularly limited, and is, for example, 10 μm to 300 μm, preferably 20 μm to 200 μm.
[0080] Generally, the positive electrode active material is in the form of secondary particles formed by the aggregation of primary particles. However, the layer 54B having a large mass ratio (S) of the surfactant preferably contains a single-particle positive electrode active material. At this time, the impregnation of the non-aqueous electrolyte into the positive electrode active material layer 54 is further improved. It can be considered that this is because: a fine grid-like penetration path of the non-aqueous electrolyte is formed in the layer 54B, and the impregnation speed of the non-aqueous electrolyte is increased due to the capillary phenomenon.
[0081] Here, a "single particle" is a particle generated by the growth of a single crystal nucleus, and is therefore a single crystal particle that does not include a crystal grain boundary. Whether a particle is a single crystal can be confirmed by analyzing an electron diffraction image using a transmission electron microscope (TEM), for example.
[0082] Single particles have the property of being difficult to aggregate, and single particles alone constitute positive electrode active material particles, but there are also cases where single particles aggregate to constitute positive electrode active material particles. However, in the case where single particles aggregate to constitute positive electrode active material particles, the number of aggregated single particles is more than 2 and less than 10. Therefore, a positive electrode active material particle is composed of more than 1 and less than 10 single particles, and a positive electrode active material particle can be composed of more than 1 and less than 5 single particles, can be composed of more than 1 and less than 3 single particles, and can be composed of 1 single particle. It should be noted that the number of single particles in a positive electrode active material particle can be confirmed by observation using a scanning electron microscope (SEM) at a magnification of 10,000 to 30,000 times.
[0083] Such single particles are different from polycrystalline particles composed of multiple crystal grains and secondary particles composed of multiple (specifically 11 or more) microparticles (primary particles) aggregated. Single particle positive electrode active materials can be prepared by a known method for obtaining single crystal particles (eg, molten salt method).
[0084] In addition, a single particle is usually larger than a primary particle when the primary particle constituting the secondary particle is a single crystal. Therefore, it is difficult to aggregate. The maximum diameter of a single particle can be greater than 0.5 μm, or it can exceed 1 μm, and further it can exceed 2 μm, or it can be greater than 3 μm and greater than 7 μm. In addition, the average maximum diameter of a single particle can be greater than 3 μm and greater than 7 μm. It should be noted that the maximum diameter of a single particle can be obtained by the distance between the farthest two points on the contour line of the single particle in the SEM image of the single particle. The SEM image can be a two-dimensional projection image of a single particle or a cross-sectional image. The average maximum diameter of a single particle can be obtained as the average value of the maximum diameters of more than 100 single particles selected at random in the SEM image.
[0085] The shape of the single particle is not particularly limited, and may be spherical, columnar, plate-like, or irregular.
[0086] From the viewpoint of further suppressing gas generation, preferably 80 mass % or more, more preferably 90 mass % or more of the surfactant contained in the entire positive electrode active material layer is contained in the layer 54B having a large mass ratio (S) of the surfactant.
[0087] In the first embodiment, a layer 54B having a large mass ratio (S) of a surfactant is disposed on the surface side of the positive electrode active material layer 54. In this case, the non-aqueous electrolyte that enters from the interface between the separator and the outer surface of the positive electrode active material layer 54 can diffuse to the entire positive electrode active material layer 54 using the layer 54B on the surface side as a flow path. Therefore, the impregnation of the non-aqueous electrolyte into the positive electrode active material layer 54 is particularly high.
[0088] However, the arrangement of the layer having a large mass ratio (S) of the surfactant in the multilayer structure of the positive electrode active material layer 54 is not limited thereto. Therefore, next, a second embodiment of the positive electrode disclosed herein will be described.
[0089] [Second Embodiment]
[0090] For the second embodiment of the positive electrode disclosed herein, use Figure 2 For explanation. Figure 2 In the positive electrode 50 ′ shown, the positive electrode active material layer 54 ′ has a multilayer structure including a layer 54C located on the positive electrode current collector 52 side and a layer 54D located on the surface layer side.
[0091] In the second embodiment, the mass ratio (S) of the surfactant in the layer 54C located on the positive electrode current collector 52 side is large, so the layer 54C corresponds to the layer 54B of the first embodiment, and the layer 54D corresponds to the layer 54A of the first embodiment. That is, the second embodiment is an embodiment in which the positions of the layer 54B having a large mass ratio (S) of the surfactant and the layer 54A having a small mass ratio (S) of the surfactant in the first embodiment are exchanged.
[0092] In this way, when a layer 54C having a large mass ratio (S) of the surfactant is arranged on the positive electrode collector 52 side of the positive electrode active material layer 54', the generation of gas can be further suppressed. This is because the surface layer of the positive electrode active material layer 54' facing the negative electrode has a large reaction load, so the surfactant is easily decomposed under high voltage, and by arranging a layer 54C having a large mass ratio (S) of the surfactant on the positive electrode collector 52 side of the positive electrode active material layer 54' (that is, arranging a layer 54D having a small mass ratio (S) of the surfactant on the surface layer side of the positive electrode active material layer 54'), the amount of the decomposed surfactant can be reduced.
[0093] [Third Embodiment]
[0094] The positive electrode active material layer of the positive electrode disclosed herein may have a multilayer structure of three or more layers. Figure 3 For explanation. Figure 3 In the positive electrode 50 ″ shown, the positive electrode active material layer 54 ″ has a multilayer structure including a layer 54E located on the positive electrode current collector 52 side, a layer 54F located in the center, and a layer 54G located on the surface side.
[0095] In the third embodiment, the mass ratio (S) of the surfactant is the largest in the layer 54F located in the center, which corresponds to the layer 54B of the first embodiment. On the other hand, the mass ratio (S) of the surfactant in the layer 54E located on the positive electrode current collector 52 side and the layer 54G located on the surface side corresponds to the layer 54A of the first embodiment.
[0096] As shown in the example, in the case where the mass ratio (S) of the surfactant is the largest in the intermediate layer (layer 54F in the example) separated from the positive electrode current collector 52 and the outer surface of the positive electrode active material layer 54, the generation of gas can be further suppressed for the same reason as in the second embodiment. In addition, since the amount of surfactant present near the positive electrode current collector 52 decreases, the increase in the interface resistance between the positive electrode active material layer 54 and the positive electrode current collector 52 can be suppressed.
[0097] When the positive electrode active material layer has a multilayer structure of three or more layers, “a layer having a large mass ratio (S) of the surfactant” means “a layer having the largest mass ratio (S) of the surfactant”.
[0098] When the positive electrode active material layer has a multilayer structure of three or more layers, the layer having a larger mass ratio (S) of the surfactant may be located on the surface layer side or on the positive electrode current collector 52 side.
[0099] [Other embodiments]
[0100] In the positive electrode disclosed herein, the distribution of the surfactant in each layer of the multilayer structure of the positive electrode active material layer may be uneven. Therefore, it is possible to have a specified concentration distribution in each layer of the multilayer structure of the positive electrode active material layer. Therefore, for example, as another embodiment, the surfactant is distributed so that the concentration of the surfactant decreases from the outer surface of the positive electrode active material layer to the positive electrode collector, and the mass ratio of the surfactant is different in the area from the outer surface of the positive electrode active material layer to 33% of the thickness (upper layer) and the area from the collector of the positive electrode active material layer to 67% of the thickness (lower layer), and in the upper layer where the mass ratio of the surfactant is high, the mass ratio of the surfactant can be 1.0 mass% or more and 10 mass% or less.
[0101] In the positive electrode constructed as above, the non-aqueous electrolyte has excellent impregnation into the positive electrode active material layer, and gas generation is suppressed. The positive electrode constructed as above can be used for the positive electrode of a secondary battery according to a known method. Therefore, the positive electrode disclosed herein is suitable for use in a secondary battery. The secondary battery can be an all-solid battery, but due to the excellent permeability of the non-aqueous electrolyte to the positive electrode active material layer, it is preferably a non-aqueous electrolyte secondary battery.
[0102] [Non-aqueous electrolyte secondary battery]
[0103] Therefore, from another perspective, the nonaqueous electrolyte secondary battery disclosed herein includes the above-mentioned positive electrode, negative electrode, and nonaqueous electrolyte.
[0104] Hereinafter, a flat square lithium-ion secondary battery having a flat wound electrode body and a flat battery case is described in detail as an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed herein, but it is not intended to limit the non-aqueous electrolyte secondary battery disclosed herein to the contents described in the embodiment.
[0105] Figure 4The lithium-ion secondary battery 100 shown is a sealed battery constructed by accommodating a flat wound electrode body 20 and a non-aqueous electrolyte 80 in a flat square battery case (i.e., an outer container) 30. The battery case 30 is provided with a positive terminal 42 and a negative terminal 44 for external connection, and a thin-walled safety valve 36 that is set to release the internal pressure of the battery case 30 when the internal pressure of the battery case 30 rises above a specified level. In addition, the battery case 30 is provided with an injection port (not shown) for injecting the non-aqueous electrolyte 80. The positive terminal 42 is electrically connected to the positive electrode collector plate 42a. The negative terminal 44 is electrically connected to the negative electrode collector plate 44a. As the material of the battery case 30, a metal material that is lightweight and has good thermal conductivity, such as aluminum, is used. To explain, Figure 4 The amount of the nonaqueous electrolyte solution 80 is not accurately indicated.
[0106] like Figure 4 and Figure 5 As shown, the wound electrode body 20 has a form in which a positive electrode sheet 50 and a negative electrode sheet 60 are overlapped and wound in the longitudinal direction via two long strip separator sheets 70. The positive electrode sheet 50 has a structure in which a positive electrode active material layer 54 is formed on one side or both sides (here both sides) of a long strip positive electrode collector 52 along the longitudinal direction. The negative electrode sheet 60 has a structure in which a negative electrode active material layer 64 is formed on one side or both sides (here both sides) of a long strip negative electrode collector 62 along the longitudinal direction. The positive electrode active material layer non-formed portion 52a (i.e., a portion where the positive electrode active material layer 54 is not formed and the positive electrode collector 52 is exposed) and the negative electrode active material layer non-formed portion 62a (i.e., a portion where the negative electrode active material layer 64 is not formed and the negative electrode collector 62 is exposed) are formed to extend outward from both ends of the winding axis direction (i.e., the sheet width direction orthogonal to the above-mentioned longitudinal direction) of the wound electrode body 20. The positive electrode current collector plate 42a and the negative electrode current collector plate 44a are joined to the positive electrode active material layer non-formed portion 52a and the negative electrode active material layer non-formed portion 62a, respectively.
[0107] The positive electrode sheet 50 uses the above-mentioned positive electrode.
[0108] On the other hand, as the negative electrode current collector 62 constituting the negative electrode sheet 60, a sheet or foil of a metal such as copper, nickel, titanium, stainless steel, etc. can be used, and copper foil is preferably used. When copper foil is used as the negative electrode current collector 62, there is no particular limitation on its thickness, and it is, for example, 5 μm or more and 35 μm or less, and preferably 7 μm or more and 20 μm or less.
[0109] As the negative electrode active material, known negative electrode active materials used in lithium ion secondary batteries can be used, for example, carbon materials such as graphite, hard carbon, and soft carbon can be used. The graphite can be natural graphite or artificial graphite, or amorphous carbon-coated graphite in which graphite is coated with an amorphous carbon material.
[0110] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is preferably 90% by mass or more, and more preferably 95% by mass or more.
[0111] The negative electrode active material layer 64 may contain components other than the negative electrode active material, such as a binder, a thickener, and the like.
[0112] As the binder, for example, styrene butadiene rubber (SBR) and its modified bodies, acrylonitrile butadiene rubber and its modified bodies, acrylic rubber and its modified bodies, fluororubber, etc. can be used. Among them, SBR is preferred. There is no particular limitation on the content of the binder in the negative electrode active material layer 64, but it is preferably 0.1 mass % or more and 8 mass % or less, and more preferably 0.2 mass % or more and 3 mass % or less.
[0113] As the thickener, for example, cellulose polymers such as carboxymethyl cellulose (CMC), methyl cellulose (MC), cellulose acetate phthalate (CAP), and hydroxypropyl methyl cellulose (HPMC); polyvinyl alcohol (PVA) and the like can be used. Among them, CMC is preferred. There is no particular limitation on the content of the thickener in the negative electrode active material layer 64, but it is preferably 0.3% by mass or more and 3% by mass or less, and more preferably 0.4% by mass or more and 2% by mass or less.
[0114] The thickness of the negative electrode active material layer 64 is not particularly limited, and is, for example, 10 μm or more and 300 μm or less, and preferably 20 μm or more and 200 μm or less.
[0115] As the separator 70, for example, a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc. can be cited. The porous sheet can be a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). A heat-resistant layer (HRL) can be provided on the surface of the separator 70.
[0116] The thickness of the separator 70 is not particularly limited, but is, for example, 5 μm or more and 50 μm or less, and preferably 10 μm or more and 30 μm or less.
[0117] The non-aqueous electrolyte 80 typically contains a non-aqueous solvent and an electrolyte salt (in other words, a supporting salt). As a non-aqueous solvent, organic solvents such as various carbonates, ethers, esters, nitriles, sulfones, and lactones used in the electrolyte of a general lithium ion secondary battery can be used without particular limitation. Among them, carbonates are preferred, and as a specific example thereof, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), etc. can be listed. Such a non-aqueous solvent can be used alone or in combination of two or more.
[0118] As the electrolyte salt, for example, LiPF 6 , LiBF 4 , lithium bis(fluorosulfonyl)imide (LiFSI) and other lithium salts, among which LiPF 6 The concentration of the electrolyte salt is not particularly limited, but is preferably 0.7 mol / L or more and 1.3 mol / L or less.
[0119] It should be noted that the above-mentioned non-aqueous electrolyte 80 may also contain components other than the above-mentioned components, such as film-forming agents such as oxalate complexes, gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); thickeners; and other various additives, as long as the effects of the present invention are not significantly impaired.
[0120] In the lithium-ion secondary battery 100 constructed as described above, the non-aqueous electrolyte 80 is easily impregnated into the positive electrode active material layer 54. Therefore, when manufacturing the lithium-ion secondary battery 100, the non-aqueous electrolyte 80 injected into the battery case 30 penetrates into the electrode body 20 in a short time, so the production efficiency is excellent. In addition, when the lithium-ion secondary battery 100 is repeatedly charged and discharged, the non-aqueous electrolyte 80 is squeezed out of the electrode body 20 as the active material expands and contracts, but the squeezed non-aqueous electrolyte 80 is easy to return to the electrode body 20. Therefore, in the lithium-ion secondary battery 100, the amount of the non-aqueous electrolyte 80 in the electrode body 20 is extremely suppressed during repeated charge and discharge, and the cycle characteristics are excellent. In addition, the generation of gas at high voltage caused by the decomposition of the surfactant in the positive electrode 50 is suppressed.
[0121] The lithium ion secondary battery 100 can be used for various purposes. As suitable purposes, a driving power source mounted on vehicles such as electric vehicles (BEV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV) can be listed. In addition, the lithium ion secondary battery 100 can be used as a storage battery for a small power storage device, etc. The lithium ion secondary battery 100 can typically be used in the form of a battery pack formed by connecting a plurality of batteries in series and / or in parallel.
[0122] As an example, a square lithium-ion secondary battery 100 having a flat wound electrode body 20 is described. However, the lithium-ion secondary battery disclosed herein may also be configured as a lithium-ion secondary battery having a stacked electrode body (i.e., an electrode body formed by alternating stacking of a plurality of positive electrodes and a plurality of negative electrodes). In addition, the non-aqueous electrolyte secondary battery disclosed herein may also be configured as a cylindrical lithium-ion secondary battery, a laminated shell lithium-ion secondary battery, a coin-shaped lithium-ion secondary battery, etc.
[0123] Furthermore, a nonaqueous electrolyte secondary battery other than a lithium ion secondary battery can also be constructed using the above-mentioned positive electrode according to a known method.
[0124] Hereinafter, examples according to the present invention will be described, but the present invention is not intended to be limited to the contents shown in these examples.
[0125] <Example 1>
[0126] The secondary particles of lithium nickel manganese cobalt composite oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 NCM811) and polyethylene glycol dimethyl ether as a surfactant were mixed in a mass ratio of 99:1 using a high-speed stirrer to obtain an active material coated with a surfactant (hereinafter also referred to as the "first active material"). In addition, a secondary particle-shaped lithium nickel manganese cobalt composite oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) and polyethylene glycol dimethyl ether (PEGDME) as a surfactant are mixed in a mass ratio of 99.5:0.5 using a high-speed stirrer to obtain an active substance coated with a surfactant (hereinafter also referred to as "the second active substance").
[0127] The first active material, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder are mixed at a mass ratio of first active material: AB: PVDF = 97.5: 1.5: 1.0, and a proper amount of N-methyl-2-pyrrolidone (NMP) is added to the obtained mixture to prepare a first positive electrode composite slurry. In addition, the second active material, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder are mixed at a mass ratio of second active material: AB: PVDF = 97.5: 1.5: 1.0, and a proper amount of N-methyl-2-pyrrolidone (NMP) is added to the obtained mixture to prepare a second positive electrode composite slurry.
[0128] The second positive electrode composite slurry is applied on both sides of the positive electrode collector made of aluminum foil and dried. Next, the first positive electrode composite slurry is applied on the dried coating of the second positive electrode composite slurry and dried. At this time, the ratio of the coating thickness of the first positive electrode composite slurry to the coating thickness of the second positive electrode slurry is set to 0.5. Then, the coating is rolled with a calender roller to prepare a positive electrode sheet. In the positive electrode active material layer after rolling, the ratio of the thickness of the layer formed by the first positive electrode composite slurry to the thickness of the layer formed by the second positive electrode composite slurry is the same as the above-mentioned coating thickness ratio, which is 0.5.
[0129] In addition, graphite (C) as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed in ion exchange water at a mass ratio of C: SBR: CMC = 97.5: 1.0: 1.5 to prepare a slurry for forming a negative electrode active material layer. The slurry for forming a negative electrode active material layer was applied to a copper foil. Then, it was dried and rolled to a specified thickness to prepare a negative electrode sheet.
[0130] As a separator, a porous polyolefin sheet having a three-layer structure of PP / PE / PE was prepared, and the positive electrode sheet and the negative electrode sheet were stacked with the separator interposed therebetween to produce a stacked (stacked) type stacked electrode body.
[0131] The electrode body is provided with electrode terminals, which are inserted into a case made of an aluminum laminate film, welded, and then injected with a non-aqueous electrolyte. The non-aqueous electrolyte is a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1. 6 The obtained non-aqueous electrolyte solution was dissolved at a concentration of 1.0 mol / L. Then, the laminate case was sealed, thereby obtaining a lithium ion secondary battery for evaluation of Example 1.
[0132] <Examples 2, 3, 5, 6 and Comparative Examples 1 and 2>
[0133] Except that the mass ratio (mass %) of the surfactant to the total of the positive electrode active material and the surfactant when making the first active material, and the mass ratio (mass %) of the surfactant to the total of the positive electrode active material and the surfactant when making the second active material are changed to the values shown in Table 1, the same operation as in Example 1 was carried out to prepare lithium ion secondary batteries for evaluation of Examples 2, 3, 5, 6 and Comparative Examples 1 and 2.
[0134] <Example 4>
[0135] A lithium ion secondary battery for evaluation of Example 4 was produced in the same manner as in Example 3 except that the second positive electrode mixed material slurry was applied after the first positive electrode mixed material slurry was applied.
[0136] <Comparative Example 3>
[0137] The secondary particles of lithium nickel manganese cobalt composite oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) and polyethylene glycol dimethyl ether as a surfactant are mixed in a mass ratio of 90:10 using a high-speed stirrer to obtain an active material coated with a surfactant (first active material). Use the same operation as in Example 1 to prepare a first positive electrode composite slurry. Using only the first positive electrode composite slurry, the positive electrode is produced in the same manner as in Example 1. At this time, the coating thickness of the first positive electrode composite slurry is adjusted so that the thickness of the positive electrode active material layer is the same as in Example 1. Except for using this positive electrode, the lithium ion secondary battery for evaluation of Comparative Example 3 is produced in the same manner as in Example 1.
[0138] <Reference Example 1>
[0139] In addition to using secondary particles of LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622) replaces LiNi secondary particles 0.8 Co 0.1 Mn 0.1 O 2 A lithium ion secondary battery for evaluation of Reference Example 1 was prepared in the same manner as in Comparative Example 3 except that (NCM811) was used as the positive electrode active material.
[0140] <Comparative Example 4>
[0141] A lithium ion secondary battery for evaluation of Comparative Example 4 was prepared in the same manner as in Comparative Example 3 except that the mass ratio of the positive electrode active material to the surfactant was changed to 99.8:0.2.
[0142] <Examples 7 to 9>
[0143] Evaluation lithium-ion secondary batteries of Examples 7 to 9 were prepared in the same manner as in Example 5, except that the coating thickness of the first positive electrode composite slurry and the second positive electrode composite slurry were changed and the ratio of the thickness of the layer formed by the first positive electrode composite slurry to the thickness of the layer formed by the second positive electrode composite slurry was changed to the value shown in Table 1.
[0144] <Examples 10 and 11>
[0145] Lithium ion secondary batteries for evaluation of Examples 10 and 11 were prepared in the same manner as in Example 5 except that the coverage of the first active material with the surfactant used in the first positive electrode composite slurry was changed to the value shown in Table 1.
[0146] <Example 12>
[0147] A lithium ion secondary battery for evaluation of Example 12 was produced in the same manner as in Example 5 except that the surfactant was changed to alkyltrimethylammonium chloride (ATMAC).
[0148] <Example 13>
[0149] In addition to using single-particle LiNi 0.8 Co 0.1 Mn 0.1 O 2 Substituting for secondary particles of LiNi 0.8 Co 0.1 Mn 0.1 O 2 A lithium ion secondary battery for evaluation of Example 13 was produced in the same manner as in Example 5 except for the positive electrode active material.
[0150] <Gas Generation Evaluation>
[0151] The volume of each evaluation lithium ion secondary battery was obtained by the Archimedes method using Fluorinert as a solvent. The volume was set as the initial volume. Next, each evaluation lithium ion secondary battery was charged to 4.3V at 25°C and allowed to stand for 5 days at 45°C. Then, the volume of each evaluation lithium ion secondary battery was obtained by the Archimedes method using Fluorinert as a solvent. The difference (mL) between the volume after charging and the initial volume was obtained and used as the amount of gas generated. The results are shown in Table 1.
[0152] <Evaluation of electrolyte impregnation>
[0153] The positive electrode prepared in each of the above test examples was cut into a size of 5 cm × 20 cm to prepare a positive electrode sample. The lower 3 cm of the positive electrode was vertically immersed in the non-aqueous electrolyte used in each of the above test examples, and the speed (cm / h) at which the electrolyte penetrated into the positive electrode active material layer was measured. It should be noted that the situation of the electrolyte penetrating into the positive electrode active material layer is grasped based on the change in the color of the positive electrode active material layer when the electrolyte penetrates. The results are shown in Table 1.
[0154] [Table 1]
[0155]
[0156] First, it can be seen from the comparison between Comparative Example 3 and Reference Example 1 that the problem of gas generation at high voltage is a unique problem caused when the Ni content in the lithium composite oxide is high (especially 70 mol% or more). In addition, it can be seen from the comparison between each embodiment and each comparative example that the positive electrode active material layer has a multilayer structure including two or more layers with different mass ratios of surfactants relative to the total mass ratio of the positive electrode active material and the surfactant. In the layer with a large mass ratio of the surfactant in the layer included in the multilayer structure, when the mass ratio of the surfactant is 1.0 mass% or more and 10 mass% or less, the non-aqueous electrolyte is excellent in impregnation into the positive electrode active material layer, and gas generation is suppressed.
[0157] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the scope of the claims includes various modifications and changes to the specific examples described above.
Claims
1. A positive electrode comprising a positive electrode current collector and a positive electrode active material layer supported on the positive electrode current collector, wherein: The positive electrode active material layer contains a positive electrode active material and a surfactant, The positive electrode active material includes a lithium composite oxide in which the content of nickel relative to metal atoms other than lithium is 70 mol % or more, The positive electrode active material layer has a multilayer structure including two or more layers having different mass ratios of the surfactant relative to the total of the positive electrode active material and the surfactant. In the layer having a large mass proportion of the surfactant among the layers included in the multilayer structure, the mass proportion of the surfactant is 1.0 mass % or more and 10 mass % or less, In the layer in which the mass proportion of the surfactant is small among the layers included in the multilayer structure, the mass proportion of the surfactant is 0.2 mass % or more and 0.5 mass % or less.
2. The positive electrode according to claim 1, wherein The ratio of the thickness of the layer having a large mass ratio of the surfactant to the thickness of the layer having a small mass ratio of the surfactant is 0.1 or more and 0.5 or less.
3. The positive electrode according to claim 1 or 2, wherein In the layer having a large mass proportion of the surfactant, the mass proportion of the surfactant is 1.0 mass % or more and 5.0 mass % or less.
4. The positive electrode according to claim 1 or 2, wherein The surfactant is a nonionic surfactant.
5. The positive electrode according to claim 1 or 2, wherein In the layer having a large mass ratio of the surfactant, the coverage of the positive electrode active material with the surfactant is 5% or more and 50% or less.
6. The positive electrode according to claim 1 or 2, wherein The layer containing a large mass proportion of the surfactant contains a single particle positive electrode active material.
7. A non-aqueous electrolyte secondary battery comprising: The positive electrode according to any one of claims 1 to 6, negative electrode, and Non-aqueous electrolyte.
Citation Information
Patent Citations
Electrode for non-aqueous electrolyte secondary battery
JP2008021415A
Lithium secondary battery containing electrode active material containing surfactant
JP2009526349A
Electrolyte for nonaqueous power storage device, and lithium ion secondary battery
JP2015201309A
Lithium ion battery electrode and preparation method thereof and lithium ion battery
CN112271270A
Manufacturing method of cathode
JP2010251047A